A highly selective and fast-response fluorescent probe for visualization of enzymatic H2S production in vitro and in living cells1. Issue 52 (4th July 2015) - Wei, Lv; Zhu, Zhentao; Li, Yanyan; Yi, Long; Xi, Zhen
<x xml:space="preserve">Abstract</x> The o-fluorinated-azido-capped rhodamine probe was developed for visualization of enzymatic H2S production both in vitro and in living cells.